2021
DOI: 10.3390/molecules26082194
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Evaluation of Urine from Patients Diagnosed with High Grade (HG) Bladder Cancer by SPME-LC-MS Method

Abstract: Bladder cancer (BC) is a common malignancy of the urinary system and a leading cause of death worldwide. In this work, untargeted metabolomic profiling of biological fluids is presented as a non-invasive tool for bladder cancer biomarker discovery as a first step towards developing superior methods for detection, treatment, and prevention well as to further our current understanding of this disease. In this study, urine samples from 24 healthy volunteers and 24 BC patients were subjected to metabolomic profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…44 In another study, the amount of benzoic acid and hippuric acid in urinary metabolites of bladder cancer patients were lower than in healthy controls, which were known to be connected with phenylalanine metabolism pathway. 45 Similar results were obtained in the current study. The amount of hippuric acid found in the urine samples of the HC group was 49.03% higher than the benign patient group and 60.13% higher than the malignant patient group.…”
Section: Discussionsupporting
confidence: 91%
“…44 In another study, the amount of benzoic acid and hippuric acid in urinary metabolites of bladder cancer patients were lower than in healthy controls, which were known to be connected with phenylalanine metabolism pathway. 45 Similar results were obtained in the current study. The amount of hippuric acid found in the urine samples of the HC group was 49.03% higher than the benign patient group and 60.13% higher than the malignant patient group.…”
Section: Discussionsupporting
confidence: 91%
“…A common strategy used to increase the efficacy of TFME blades is an implementation of chemistries theoretically more suited for the use with aqueous samples than the conventional C 18 . Most popular solutions include mixed-mode C 18 (octadecyl with strong cationic exchanger of benzenesulfonic acid) [ 18 , 19 ], polar enhanced (with unspecified weak anionic exchanger) polystyrene-divinylbenzene (PS-DVB) [ 18 , 19 , 20 , 22 , 23 , 24 ], hydrophilic-lipophilic balance (HLB) [ 11 , 20 , 21 , 22 ], and phenylboronic acid (PBA) [ 18 , 19 , 20 , 22 , 23 ] coatings. However, the selection of optimal chemistry is highly dependent on target analytes and their proprieties, with each coating characterised by its unique advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The authors’ study reported elevated levels of these metabolites in the sera of patients with bladder tumors compared to those of patients with early stages of BC [ 80 ]. In contrast, an LC-MS-based study reported lower levels of histidine in the urine of patients with BC compared to healthy controls [ 56 , 81 ]. Moreover, Li et al.…”
Section: Discussionmentioning
confidence: 99%